Identification and Functional Characterization of the Soybean GmaPPO12 Promoter Conferring Phytophthora sojae Induced Expression - Chai, Chunyue (Public Library of Science, 2013)
Identification of pathogen-inducible promoters largely lags behind cloning of the genes for disease resistance. Here, we cloned the soybean GmaPPO12 gene and found that it was rapidly and strongly induced by Phytophthora sojae infection. Computational analysis revealed that its promoter contained many known cis-elements, including several defense related transcriptional factor-binding boxes. We showed that the promoter could mediate induction of GUS expression upon infection in both transient expression assays in Nicotiana benthamiana and stable transgenic soybean hairy roots. Importantly, we demonstrated that pathogen-induced expression of the GmaPPO12 promoter was higher than that of the soybean GmaPR1a promoter. A progressive 5’ and 3’ deletion analysis revealed two fragments that were essential for promoter activity. Thus, the cloned promoter could be used in transgenic plants to enhance resistance to phytophthora pathogens, and the identified fragment could serve as a candidate to produce synthetic pathogen-induced promoters.